2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090067
|View full text |Cite
|
Sign up to set email alerts
|

Variability of hand tremor in rest and in posture — A pilot study

Abstract: Previous, studies have demonstrated variability in the frequency and amplitude in tremor between subjects and between trials in both healthy individuals and those with disease states. However, to date, few studies have examined the composition of tremor. Efficacy of treatment for tremor using techniques such as Botulinum neurotoxin type A (BoNT A) injection may benefit from a better understanding of tremor variability, but more importantly, tremor composition. In the present study, we evaluated tremor variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 6 publications
0
13
0
2
Order By: Relevance
“…This demonstrates that the smart phone can provide a reliable measure of tremor of different amplitudes. This is important as it is well known that while not all PD patients exhibit tremor, those that have tremor can exhibit highly variable tremor amplitude and that this amplitude can fluctuate over short periods of time (Duval et al, 1997; Duval and Beuter, 1998; Rahimi et al, 2011). Tremor severity can also fluctuate within a given day and over multiple days which makes long-term monitoring of patients a necessity.…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates that the smart phone can provide a reliable measure of tremor of different amplitudes. This is important as it is well known that while not all PD patients exhibit tremor, those that have tremor can exhibit highly variable tremor amplitude and that this amplitude can fluctuate over short periods of time (Duval et al, 1997; Duval and Beuter, 1998; Rahimi et al, 2011). Tremor severity can also fluctuate within a given day and over multiple days which makes long-term monitoring of patients a necessity.…”
Section: Discussionmentioning
confidence: 99%
“…Tools that actually measure this amplitude would therefore be justified as being more consistent. Consequently, similar to other such studies [18,31,32,34,35], this study is also lacking the comparison of the proposed high-resolution system with a widely accepted kinematic tool.…”
Section: Emerging Technologiesmentioning
confidence: 95%
“…Although PD tremor is classically a rest tremor, our prior work has shown that postural tremor is significant in PD [7,18,31]. The duration of this task was designed to include the re-emergent tremor.…”
Section: Development Of Tss Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Starting from the accelerometer [10] data is possible to quantify the amplitude of oscillations and particularly the intensity of tremor at the various frequencies in the spectrum through the Power Spectral Density (PSD). This also allows an estimate of how much the tremor is disabling for the patient by limiting his normal activities into daily routine.…”
Section: A Acquisition Systemmentioning
confidence: 99%